COMMUNICATIVE COMPETENCE: PRINCIPLES AND METHODS OF SHAPING (Proceedings of International Educators Conference, 2023)
This article explores the principles and methods of shaping communicative competence. It highlights the significance of effective communication in various contexts and provides insights into the key elements necessary for developing communicative competence. The article presents different methods that can be employed to enhance communicative competence and discusses the results, implications, and potential areas for further research.